Labour market institutions and unemployment revisited - Carsten Ochsen (Universität Rostock, Institut für Volkswirtschaftslehre, 2005)
In this paper the effects of institutional variables on unemployment are reinvestigated for nine OECD countries. The used framework allow for country specific estimates. In this case, the impact of the considered institutional variables on unemployment may differ across countries, not only in absolute terms but also in terms of sign. The main results are the following: First, there are remarkable differences across countries with respect to the estimated effects. Most of the considered variables have at least in one of the considered countries an unexpected effect. Secondly, after a careful examination of the results we identify complex interdependencies between the institutional variables, which bear resemblance to the interaction hypothesis. Thirdly, the estimates with respect to the minimum wage do confirm the theory of monopsonistic labour markets. Fourthly, based on a cross country comparison some evidence is found that some of the considered labour market institutions have a hump-shaped or U-shaped relation to the unemployment rate. All things considered, the results make strong distinctions clear, and the different economies should be extremely cautious to make a copy of the level of a certain labour market institution of the neighbours.
Keywords: J60; E24; J50; H55; 330; Beveridge-Curve; employment determination; labour market rigidities; social security